THE CONCEPT OF NEW HISTORICISM IN INDONESIAN LITERATURE - Nurhasanah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This article discusses the concept of New Historicism and its application in Indonesian literature, which emphasizes the close relationship between literary works and the social, political, and cultural contexts that underlie them. New Historicism argues that history is not an absolute truth, but a discourse consisting of various versions and points of view. In this study, literary works are seen as cultural reflections and historical documentation, which represent the struggles and values of society in a certain period. Through this approach, literary and non-literary texts interact with each other, creating a deeper understanding of the historical and ideological contexts that influence literary works. This research also highlights the importance of further exploration of the contribution of literature in shaping Indonesia's cultural identity and its relevance to contemporary social issues.